Why and when does job satisfaction promote unethical pro‐organizational behaviours? Testing a moderated mediation model. (20th September 2018) - Dou, Kai; Chen, Yushuai; Lu, Junming; Li, Jingjing; Wang, Yujie
Abstract : This study examined the relationship between job satisfaction and unethical pro‐organizational behaviours (UPB) by testing a moderated mediation model that focused on how employees' belongingness mediates the relationship between job satisfaction and UPB and how corporate ethical values moderate this mediated relationship. Our investigation included 369 employees from different organizations in Southeast China. The regression analysis revealed that job satisfaction positively influences UPB through belongingness. In addition, a moderated regression analysis indicated that low corporate ethical values strengthen not only the effect of belongingness on UPB but also the indirect effect of job satisfaction on UPB. These findings deepen our understanding of UPB by showing that individuals with a high level of job satisfaction are more likely to engage in UPB through belongingness when corporate ethical values are low. Finally, the theoretical and managerial implications of these results are discussed.